BOUNDARY SEPARATION AND BINDING ENERGY OF ATOMS IN THE REAL SURFACE OF A SOLID - Bozorov Nasirjon Sodikovich, Umurkulov Kayumjon Parpievich, Alisherov Otabek Alisher son; Abdumanonova Firuza Abdualiyevna (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents the main prefix about the structure of the crystal, the energy of interaction, the laws of surface phenomena. Energy exchange between gas atoms and the surface. The physical aspects of energy interaction are considered.